Small Forms of Wooden Architecture of the Russian North: Fences, Gates, Wicket Doors and Retaining Walls - Olga Sevan (Proekt Bajkal, 2013)
The article studies historical and modern aspects of design and building of small architectural forms (fences, gates, wicket doors, retaining walls and partially – bridge fences) in many regions of the Russian North and other regions of Russia. This work is based on the author’s investigations of the great number of monuments of wooden architecture during the visit to several regions of Russia in connection with preparation of the Collection of Monuments and the building of open-air museums in the Vologda and Arkhangelsk regions (“Malye Korely”). The author suggests her own systematization of the above-mentioned constructions, most of which have eventually become monuments of folk architecture. The majority of the discovered and measured small architectural forms are reconstructed in the museums. They can be also easily built in the real environment of rural settlements, small towns, country estates and dacha communities of the mentioned regions.